Clinicopathological analysis of primary refractory diffuse large B‐cell lymphoma treated with rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisolone chemoimmunotherapy. (9th June 2021) - Suzuki, Tomotaka; Maruyama, Dai; Miyagi‐Maeshima, Akiko; Nomoto, Junko; Tajima, Kinuko; Ito, Yuta; Hatta, Shunsuke; Yuda, Sayako; Makita, Shinichi; Fukuhara, Suguru; Munakata, Wataru; Suzuki, Tatsuya; et al.
Abstract: Background: Approximately 15% of patients with diffuse large B‐cell lymphoma (DLBCL) experience refractory or early relapsed disease after initial rituximab‐containing chemoimmunotherapy is regarded as a primary refractory disease. Although the standard treatment for relapsed DLBCL is high‐dose chemotherapy and autologous stem cell transplantation (HDC‐ASCT), the efficacy of this approach for primary refractory DLBCL is not well understood. We aimed to investigate the clinicopathological characteristics and outcomes of patients with primary refractory DLBCL. Methods: Sixty‐nine consecutive patients with primary refractory DLBCL who were treated at our institution were categorized as partial responders (partial response to rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisolone [R‐CHOP] or relapse within 6 months of R‐CHOP) ( n  = 41) or primary progressors (no response to R‐CHOP) ( n  = 28). Survival curves were constructed using the Kaplan–Meier method and compared using the log‐rank test. Results: At initial diagnosis, 70% of patients had Ann Arbor stage III/IV disease, 56% had non‐germinal center B‐cell‐like type DLBCL, and 42% had double‐expressor lymphoma (MYC and BCL2 expression). The 3‐year overall survival rate was significantly poorer in the primary progressors group than in the partial responders' group (15% vs. 48%, p  < 0.001). Four of 17 patients treated with HDC‐ASCT were primary progressors; only one patient survived without relapse. Although double‐expressor lymphoma status did not significantly impact overall survival among all patients ( p  = 0.794), it was identified as an independent poor prognostic factor in HDC‐ASCT‐treated patients ( p  = 0.002). Conclusions: We identified a subgroup of patients with primary refractory DLBCL who may not benefit from current treatment strategies. Further treatment development is needed to improve the outcomes of these patients. Abstract : Sixty‐nine consecutive patients with primary refractory DLBCL who were treated at our institution were clinicopathologically analyzed.We identified a subgroup of patients with primary refractory DLBCL, including primary progressors (no response to R‐CHOP) or those with the double expression of MYC and BCL2, who may not benefit from current treatment strategies.Further treatment development is needed to improve the outcomes of these patients.